Dampak Kenaikan Harga Bahan Bakar Minyak Terhadap Sembilan Bahan Pokok Di Kecamatan Tobelo - Posi, Sahrul Hi.; Muhammad, Irsad (JIMAD : Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the impact of the increase in fuel prices for nine basic commodities in the Modern Market, Tobelo District, North Halmahera Regency. The research method used is descriptive analysis with percentage calculations to determine the composition of the respondents. The data used in this study was by distributing questionnaires to 30 traders working in the Tobelo City Modern Market. The results of the study show that the impact of the increase in fuel prices (BBM) on nine basic commodities seen from several indicators and the responses of respondents include a negative impact with a percentage of 100%, it can be concluded that the increase in fuel prices has a negative impact on nine basic commodities in Tobelo District.